Numerical Study Effect of Fluidizing Air to Erosion Pattern in Circulating Fluidized Bed Boiler - Bambang Sudarmanta; Rizki Mohammad Wijayanto; Giri Nugroho; Achmad Syaifudin; Atok Setiyawan; Julendra B. Ariateja (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2017)
Bed material particles in a Circulating Fluidized Bed (CFB) boiler which entrained in the flue gas may cause material degradation due to abrrasive and high velocity impact of particles to wall surface. In this study, Computational Fluid Dynamic (CFD) commercial software with Eulerian multiphase is used to study the erosion pattern in several different fluidizing air velocity. The result obtained from simulation in terms of particles volume fraction and particles velocity in selected area was utilised to predict the erosion rate in several different fluidizing air velocity to achieve the optimal value of fluidizing air velocity. The results obtained in this study are helpful to understand how erosion pattern in CFB boiler, how effect fluidizing air velocity to erosion rate, and also helped to know the potential areas occur erosion so helped to choose suitable material in different region.